2020
DOI: 10.1002/jbm.a.36911
|View full text |Cite
|
Sign up to set email alerts
|

In vitro observation of macrophage polarization and gingival fibroblast behavior on three‐dimensional xenogeneic collagen matrixes

Abstract: Collagen biomaterials are widely used for soft tissue augmentation. Cross‐linking techniques for collagen matrix (CM) achieve mechanical and volumetric stability; nevertheless, cross‐linking may compromise biocompatibility. The aim of the present study was to investigate two different three‐dimensional (3D) porcine‐derived CMs, noncross‐linked (ncl)_CM and cross‐linked (cl)_CM, for their effects on macrophages (Mφ) and gingival fibroblasts. The effects of the CMs on the cell viability, proliferation, and polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…Traditional methods, such as the paraffin embedding procedure, require decalcification and liquid handling, which destroys the fragile structure of cells cultured in vitro on materials. Moreover, Transwell ® inserts, whose membranes allow only liquid passage, successfully maintained granule stability during the liquid handling and the collection of samples in 24-well plates, as previously reported [17]. Different cell localization was clearly observed between DBBM granules and blocks by ALP staining of Saos-2 cells, showing a marked increase in ALP expression surrounding all DBBM granules.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Traditional methods, such as the paraffin embedding procedure, require decalcification and liquid handling, which destroys the fragile structure of cells cultured in vitro on materials. Moreover, Transwell ® inserts, whose membranes allow only liquid passage, successfully maintained granule stability during the liquid handling and the collection of samples in 24-well plates, as previously reported [17]. Different cell localization was clearly observed between DBBM granules and blocks by ALP staining of Saos-2 cells, showing a marked increase in ALP expression surrounding all DBBM granules.…”
Section: Discussionsupporting
confidence: 72%
“…THP-1-derived M0 Mϕs and Saos-2 cells were seeded on either DBBM granules or blocks at a density of 1.0 × 10 5 cells per insert, in 6.5 mm Transwell inserts with 0.4-µm pore polycarbonate membranes in 24-well plates. After 3 days for THP-1 cells, and after 14 days for Saos-2 cells, the cells were fixed in 4% paraformaldehyde for 15 min, and immediately frozen in Super Cryoembedding Medium (SCEM; Section-Lab, Hiroshima, Japan) in the stainless steel container as previously described [17]. Sections (10 µm) were cut by a cryomicrotome (Microm HM550, Thermo) with an adhesive film (Cryofilm Type 2C (16UF), Section-Lab) using Kawamoto's film method [18].…”
Section: Undecalcified Frozen Section Preparation and Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…After taking the conditioned medium into consideration, the apoptotic rate of fibroblasts on TCP, BMZ, CSGZ, and SGZ surfaces reduced by 1.84, 3.67, 5.22, and 3.42%, respectively, compared with their respective controls (Figure 6), which indicated that CM collected from RAW264.7 culture in all samples slightly inhibited the apoptotic effect on fibroblasts. The conditioned medium from M2 macrophages has been shown to affect fibroblast behavior which secrete extracellular matrix (ECM), specifically collagen that can enhance efficacious implant integration (Fujioka-Kobayashi et al, 2020). Our Western blotting results showed that fibroblasts cultured with CM on BMZ surfaces produce more ECM with a higher expression of COL-I, VCL, and FN as compared with those on CSGZ and SGZ surfaces (Figures 8A-D).…”
Section: Discussionmentioning
confidence: 84%
“…For instance, it was reported that the glutaraldehyde cross-linked collagen membranes demonstrated lower cell attachment and viability when compared to non-cross-linked collagen membranes in human gingival fibroblasts [9]. Nevertheless, our previous in vitro study proved the excellent cytocompatibility of the chemically cross-linked Cl_CM as well as Ncl_CM on human THP-1-derived macrophages Materials 2021, 14, 3740 2 of 11 and gingival fibroblasts [10]. However, slight immune cell responses were observed with the higher mRNA levels of M1 markers, including interleukin (IL)-1 and IL-6, in the macrophages cultured on Cl_CM [10].…”
Section: Introductionmentioning
confidence: 86%